2021
DOI: 10.1097/wnr.0000000000001760
|View full text |Cite
|
Sign up to set email alerts
|

The distinct roles of various neurotransmitters in modulating methamphetamine-induced conditioned place preference in relevant brain regions in mice

Abstract: Objectives Previous studies have shown that methamphetamine (METH) can induce complex adaptive changes in the reward system in the brain, including the changes in the content of neurotransmitters in the signal transduction pathway. However, how the changes of various neurotransmitters in relevant brain reward circuits contribute to METH-induced conditioned place preference (CPP) remains unclear.Methods In this study, first, we designed an animal model of METH-induced CPP. Then we used liquid chromatography-mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Another example is illustrated by comparing our study with the one of Su et al .. In this case, Su et al ., used a similar LC-MS/MS approach than in the present study to quantify most of the neurotransmitters in key brain regions involved in methamphetamine-induced conditioned place preference in C57BL/6J male mice [49]. Noradrenaline levels in the Cpu were reported to be around 0.05 μg/g of wet tissue ( i.e ., 0.30 pmol/mg of wet tissue) in control mice while in our study, we observed 5.09 ± 0.8 and 4.62 ± 0.9 pmol/mg of protein of noradrenaline in the Cpu of male and female CT mice respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another example is illustrated by comparing our study with the one of Su et al .. In this case, Su et al ., used a similar LC-MS/MS approach than in the present study to quantify most of the neurotransmitters in key brain regions involved in methamphetamine-induced conditioned place preference in C57BL/6J male mice [49]. Noradrenaline levels in the Cpu were reported to be around 0.05 μg/g of wet tissue ( i.e ., 0.30 pmol/mg of wet tissue) in control mice while in our study, we observed 5.09 ± 0.8 and 4.62 ± 0.9 pmol/mg of protein of noradrenaline in the Cpu of male and female CT mice respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our approach was designed to provide enough statistical power to understand the impact of sex on neurotransmitter levels during acute and chronic treatment with morphine. In the literature, several studies have successfully attempted to quantify neurotransmitters in the same brain regions [44][45][46][47][48][49][50][51]. However, in most cases, the levels of a single neurotransmitter were assessed in a unique brain region of male animals, and/or the methodology differs markedly between studies, yielding difficult comparisons to interpret.…”
Section: Methodology For Neurotransmitters Quantification In Males An...mentioning
confidence: 99%